Between housewifery and emancipation in My Lecturer My Husband novel by Gitlicious - Tristanti Apriyani; Xiao Lixian (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
This study aims to examine the actualization of women in the novel My Lecturer My Husband by Gitlicious by relying on the formulation put forward by Betty Friedan. The depiction of the minimal role of women in literary production means that female characters in literary works are often portrayed as biased and one-sided. Therefore, it is essential to discuss women's experiences through women authors' works because they have direct experience in describing women's lives. This research is a type of qualitative descriptive research that uses documentation techniques and literature studies as a data collection method. Meanwhile, the data analysis technique used was interactive, including data reduction techniques, presentation, and verification. This study shows that women experience an identity crisis because they often surrender to the situation. Circumstances that require Inggit's character to be at a certain point so that she feels have to return to their nature.